Hypoxia drives the formation of lung micropapillary adenocarcinoma-like structure through hypoxia-inducible factor-1α - Daisuke Umeda; Akikazu Harada; Daisuke Motooka; Shinichiro Tahara; Masako Kurashige; Kansuke Kido; Tsuyoshi Takashima; Hiroki Kiyokawa; Koto Ukon; Takahiro Matsui; Shinji Matsumoto; Yasushi Shintani; et al. (Scientific Reports)
Abstract Micropapillary adenocarcinoma (MPC) is an aggressive histological subtype of lung adenocarcinoma (LUAD). MPC is composed of small clusters of cancer cells exhibiting inverted polarity. However, the mechanism underlying its formation is poorly understood. Here we show that hypoxia is involved in MPC formation. Hypoxia induced the formation of MPC-like structures (MLSs) in a three-dimensional culture system using A549 human LUAD cells, and HIF-1α was indispensable for MLS formation. RNA sequencing analysis demonstrated that A549 cells forming MLSs exhibited a gene expression signature similar to that of lung MPC. Moreover, MLS formation enhanced the resistance of A549 cells to natural killer cell cytotoxicity. Our findings suggest that hypoxia drives lung MPC formation through HIF-1α and that immune escape from natural killer cells might underlie the aggressiveness of MPC.